A comparative study of Bay Hills Hotel constructed under Goldsands Hotels and Resorts Ltd. with other hotels present in the sector of tourism in Cox’s Bazar - Hossain, Tamhid Eshad (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.